Analisa Pengaruh Filler Metal Zinc Terhadap Sifat Mekanik Sambungan Beda Material Pada Las Titik Antara Baja Tahan Karat Dan Aluminium - Mastika, Sesa Jati, Muh. Alfatih Hendrawan, ST, MT, Dr. Supriyono (2016)
Availability of fossil fuels dwindling human demands for innovation in energy savings. An engine with high fuel efficiency is one solution to the energy savings that can be obtained by reducing vehicle weight. The type of material used will affect the weight of the vehicle. Stainless steel and aluminum is a material that can not be separated in the automotive industry. However, in the manufacturing process, the connection between stainless steel by welding is difficult because its melting point is much different. This study tried to determine the strength of welded joints different points using a filler material with or without filler. Research uses ferrite type stainless steel 1 mm thick 430 series and 6019 series aluminum 1.2 mm thick zinc with 0.2 mm thick as filler. Welding process using spot welding machine brands Dayok 0K-25 models. Specimens were divided into 2 groups: without filler and without filler with variations in current 6000 A, 7000 A and 8000 A. The time variation is 0.2 s; 0.3 s; and 0.4 s. Tests were conducted to determine the mechanical properties of welded joints that point shear testing (Shear Load Bearing Capacity) and microhardness Vickers hardness testing. Shear testing using standard testing ASME IX. While the Vickers hardness testing using standard testing microhardness AWS D8.9-97. Result showed that the addition of zinc filler metal with a variety of current and time weld significantly influence the strength of the weld joint. Similarly, the results of hardness test specimen in which an escalation of violence that was significant at the weld joint areas compared with the parent metal. For optimum welding joint force occurred on the specimen using a zinc filler metal at 8000 A current variation and a time of 0.4 seconds with a value of 1235.165 N. The highest hardness values are also present in the area of the weld metal (nugget) specimens using a filler with a current of 8000 A and a time of 0.4 seconds.